2022
DOI: 10.1093/rheumatology/keac261
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal ultrasound for treating rheumatoid arthritis to target—a systematic literature review

Abstract: Objective We aimed to systematically review the literature to retrieve evidence on the diagnostic and prognostic value of musculoskeletal ultrasound for a treat to target (T2T) approach in rheumatoid arthritis (RA). Methods Eight research questions were developed addressing the role of ultrasound (including different ultrasound scores and elementary lesions) for diagnosis, monitoring and prognosis of RA. PubMed and Embase wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…A recent systematic review on the use of musculoskeletal ultrasound for treating RA to target revealed that ultrasonography is superior to clinical assessment in diagnosing joint involvement using MRI as a reference imaging modality (32). With this present study demonstrating that thermography at the wrist of RA patients closely mirror those from ultrasonography, two interesting questions that arise are as follows: (1) whether thermal imaging may similarly have some advantage(s) over clinical assessment and (2) whether thermography could have a place as an adjunctive tool in the routine assessment of joint inflammation in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on the use of musculoskeletal ultrasound for treating RA to target revealed that ultrasonography is superior to clinical assessment in diagnosing joint involvement using MRI as a reference imaging modality (32). With this present study demonstrating that thermography at the wrist of RA patients closely mirror those from ultrasonography, two interesting questions that arise are as follows: (1) whether thermal imaging may similarly have some advantage(s) over clinical assessment and (2) whether thermography could have a place as an adjunctive tool in the routine assessment of joint inflammation in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided synovial biopsy has become popular among those examining the synovium for research 8 and may become important to the practicing clinician as rheumatologic treatment moves to becoming "precision based." 9,10 Synovial features, without biopsy, utilizing power Doppler detecting red blood cell movement that can serve as a surrogate marker for the presence and intensity of synovitis, have been extensively studied 11 and proposed as an outcome measure for treatments of inflammatory arthropathies, although the utility of such techniques remains unsettled. 12 Media comprised tiny gas-filled microbubbles, injected intravenously before US examination, and enhanced the signal reflected by vascularized structures such as inflamed synovium.…”
Section: Ultrasoundmentioning
confidence: 99%
“…The future of Boolean remission in rheumatic diseases holds promise with the integration of emerging technologies and biomarkers [ 30 ]. Advanced imaging techniques, such as musculoskeletal ultrasound and magnetic resonance imaging, can provide detailed assessments of joint inflammation and damage [ 31 ]. Biomarkers, including genetic markers and novel serological indicators, may enhance the accuracy and specificity of Boolean remission criteria [ 32 ].…”
Section: Reviewmentioning
confidence: 99%